Gaps in knowledge and practice on dietary consumption among rural farming households; a call for nutrition education training in Tanzania. (2nd April 2020) - Bundala, Nyamizi; Kinabo, Joyce; Jumbe, Theresia; Bonatti, Michelle; Rybak, Constance; Sieber, Stefan
Abstract: Dietary-related conditions are preventable only if people have better understanding of factors that underpin their dietary choices. A cross-sectional study was carried out to examine levels and gaps of nutrition knowledge and practices (KPs) of 663 mothers/caregivers in rural households of Tanzania. Results indicated that, only 14% of the population had received nutrition education prior to the survey. The mean KP score was 6.9 (±2.6) out of 20 with only 17% of the study population had KP scores above the mean. The average proportion of those who had correct responses above mean was 27% for knowledge and 22% practices. Low coverage of nutrition education and poor participation of men in nutrition education activities were frequently reported as the barriers for adoption of desirable dietary practices at households. The KP levels are far below the recommended FAO thresholds and entail high levels of nutrition illiteracy which call for immediate intervention.